Preliminary study of craniofacial superimposition by Mathematics programming in a Thai population - Jetniphit S; Thiti M; Phruksachat S; Pasuk Mahakkanukrauh (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Craniofacial superimposition are used in cases where one has found an unknown human skull. The purpose of this research was to develop craniofacial superimposition by applying mathematical programme to increase the credibility of craniofacial superimposition in Thailand. To calculate the overlay position of face-real skull photo and face photo from the same owner were compared to the face-randomised skull photo and face photo. This study was carried out on a sample of 20 skulls, divided into 10 male skulls and 10 female skulls. All samples of bones were taken from the Forensic Osteology Research Center (FORC), Faculty of Medicine, Chiang Mai University. Skull and face photography of the deceased took only the front-straight face position. The similarity was found out from edges of them that compared at important points with the mathematical programme, in which the researchers applied functions and mathematical principles of matrix and logical. In each individual experiment between face-real skull and face-randomised skull, the results were recorded and explained in the form of qualitative experiments. From the experiment found that the used programme can be able to correctly assess the similarity are 19 cases of 20 cases. Craniofacial superimposition can save the budget of DNA testing and can be screening for the initial assumption. This research will be able to facilitate, work faster, more reliable and save budget in the identifying process.